2021
DOI: 10.7759/cureus.16017
|View full text |Cite
|
Sign up to set email alerts
|

Depression Impairs Level of Functioning in Chronic Kidney Disease Inpatients: A Case-Control Study

Abstract: To evaluate the difference in demographics and clinical correlates during hospitalization for chronic kidney disease (CKD) between patients with depression and those without depression, and its impact on the severity of illness and in-hospital mortality. MethodsWe conducted a case-control study and included 2,296 adult inpatients (age ≥18 years) with a primary discharge diagnosis of CKD using the nationwide inpatient sample (NIS). We used propensity score matching to extract the cases i.e., CKD inpatients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
3
1
Order By: Relevance
“…This contrasts with a previous study that showed a strong association between disease comorbidities and depression in CKD [20]. A similar study also found an association between depression in CKD and comorbidities and suggested that depression can lead to the exacerbation of comorbid conditions [21]. Patients with CKD are known to experience depression at higher rates when they have diabetes.…”
Section: Discussioncontrasting
confidence: 86%
“…This contrasts with a previous study that showed a strong association between disease comorbidities and depression in CKD [20]. A similar study also found an association between depression in CKD and comorbidities and suggested that depression can lead to the exacerbation of comorbid conditions [21]. Patients with CKD are known to experience depression at higher rates when they have diabetes.…”
Section: Discussioncontrasting
confidence: 86%
“…2,37 Moreover, the prevalence estimate in this study is conservative, since a proportion of patients excluded by protocol might also be depressed at discharge: a) those surviving patients who were very ill at the time of admission; and b) those excluded because of low cognitive performance or substance abuse since both these clinical conditions have been associated with depression. 38,39 In relation to the clinical significance of the findings, a number of previous reports reviewed in the introductory section have documented the negative consequences of depression in medical patients, 3,36,8,21,40 which may be worse in older individuals such as those predominating in our particular study. 5,21 Complications in the patients' management have also been reported.…”
Section: Discussionmentioning
confidence: 66%
“…These findings differ from those of Silva et al [ 46 ] and Bapat et al [ 47 ]. Depression can lead to poorer health outcomes [ 48 ], increased hospitalisation [ 49 ], and lower quality of life [ 50 ]. Additionally, it was discovered that medication nonadherence is linked to worsening of CKD [ 51 ].According to Meng et al, depression and worsening CKD together increase the risk of both cardiovascular and all-cause death.…”
Section: Discussionmentioning
confidence: 99%